Importance of sampling design using an eDNA monitoring approach for pond-living amphibians - Mittl, Sabrina (2017)
The eDNA approach for monitoring aquatic species is already widely used. However, there are still uncertainties, for instance regarding the distribution of target DNA in ponds. These uncertainties need to be addressed when using eDNA in management. The current study uses individual capture and eDNA monitoring methods based on bottle trapping and 3x15 ml water sampling for Triturus cristatus in different ponds to show the importance of a carefully considered and performed study and in particular sampling design for achieving reliable results. Most of the results were received from only one pond. While here the bottle trapping resulted only in 15 catches, the eDNA method showed better results in confirming presence of the target. Examining two different primer combinations, the one with the bigger amplicon was more reliable than the one with the shorter amplicon. However, the data clearly indicated an influence of the sampling location on the eDNA results. This is also true for weather factors and / or sample time within the season. Therefore the sampling design has to be reconsidered, with respect to DNA distribution and persistence, seasonal habitation differences of the target and the primer specifics.